Psychological aspects of formation of pedagogical competence of teachers of preschool educational organization (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is one of the topical issues of today, and the scientific theoretical literature devoted to the study of the psychological aspects of the formation of pedagogical competence of educators of preschool education organizations is analyzed.